PELESTARIAN DAN PEMBINAANUSAHA JASA OJEK DOKAR DAN BECAK DI PASAR TRADISIONAL MALANG - Sunaryo Sunaryo; Margianto Margianto; Usman Ali (LPPM UNS, 2016)
Science and technology for society (IbM) is intended for business partners of Ojek coachman gig and pedicab drivers are available in traditional markets Merjosari, Lowokwaru, Malang. The IbM program is aimed to preserve transport people, improve performance coachman gig and pedicab drivers, and enhance the capabilities and employability at a time of family welfare partners. Specific targets to be achieved IbM programs that ease the workload of partners and increase revenue and improve motorcycle taxi transportation service so well that the partner revenue increased. To achieve the objectives and targets of this IbM program, a team of devotees using methods which include socialization, counseling and training motorcycle, helping modification rickshaw ontel be Pedicab, free service motor tricycles, improvement of physical performance rickshaws and carts, fermentation and formula feed concentrate high energy horse, coaching and mentoring efforts. The IbM program results indicate that all the activities responded well by partners coachman gig and a pedicab driver. Performance rickshaws and carts, and the performance of the motorcycle taxi drivers and coachman more attractive, growing customer segment, the knowledge and skills of motorcycle taxi drivers bentor about light treatment increases, the coachman gig have knowledge and skills in making the concentrate feed for his horse. Furthermore, the partner revenue increased as efforts can preserve local culture. The output of this program is the product of horse feed concentrate nutritious and high energy, modif bentor and journal articles. Conclusions from the implementation of the program is to improve the performance IbM bentor, carts, rickshaw drivers so as to increase the number of subscribers and revenues as capital to preserve its business.Keywords:traditional taxi, concentrate, business performance